Biocarbon projects in agroforestry: lessons from the past for future development - Foster K; Neufeldt, Henry (Elsevier, 2014)
Biocarbon projects can connect climate finance to smallholder farmers and can provide considerable benefits to improved productivity, land health and income, market access, institutional stability and, ultimately, food security and reduced poverty for asset-poor rural communities. While most biocarbon projects focus on forested land or tree plantations, this paper explores the potential for connecting agroforestry approaches with carbon benefits. Drawing on experiences in Africa, we identify the major challenges and opportunities for developing and rolling out biocarbon projects in agroforestry systems. We highlight the need for external, up-front funding to overcome high project establishment costs and the need for innovative solutions to minimize trade-offs between livelihood and environmental goals. We contend that resource constraints, flexibility, technical capacity, tenure and institutional frameworks must be addressed for smallholders to invest in and benefit from carbon projects. Lastly, we argue that projects should emphasize non-carbon benefits, using carbon revenue as a tool to help farmers transition to more sustainable and productive practices on their land.